Multilayer Laue Lens: A Brief History and Current Status. Issue 4 (3rd July 2016) - Conley, Ray; Bouet, Nathalie; Chu, Yong S.; Huang, Xiaojing; Kang, Hyon Chol; Macrander, Albert T.; Maser, Jörg; Nazaretski, Evgeny; Stephenson, G. Brian; Yan, Hanfei
Abstract : X-rays are intrinsically capable of being used for the study of non-periodic objects with atomic resolution, with high penetration, in applied electromagnetic fields, and in fluids and gases. For direct imaging via nanofocused X-ray beams, reflective [1 ], refractive [2 ], and diffractive [3, 4 ] optics are used in various approaches for high-resolution imaging. Diffractive X-ray optics are endowed with the highest numerical aperture, in principle allowing focusing of X-rays to sub-nanometer dimensions. Lithographically produced Fresnel zone plates (FZP) find broad deployment around the globe, in both nanofocusing and full-field imaging approaches, and have, for many years, been workhorse optics in both synchrotron-based and laboratory-based X-ray imaging systems [4 ]. A FZP consists of a series of radially symmetric rings, which are known as Fresnel zones, which alternate between transparent and opaque. Radiation traversing into the FZP diffracts around the opaque zones, which are placed in an arrangement where light constructively interferes at the focal plane.